Isolation and characterisation of novel DNA aptamers against Mycobacterium tuberculosis biomarkers: new tools for tuberculosis diagnostics - Amos-Brown, Bianca (Division of Chemical and Systems Biology, 2019)
Tuberculosis is a curable disease with an average treatment success rate of 86 %. Despite this, there were an estimated 1.5 million deaths due to tuberculosis in 2013, most of which occurred in low and middle income countries. In order to overcome tuberculosis in developing countries innovation in diagnostics is key to administering treatment. While detection of whole mycobacteria has been favoured in the past to diagnose tuberculosis, culturing mycobacteria is costly and microscopy is often not sensitive enough due to low bacterial loads. Detection of Mycobacterium tuberculosis biomarkers in urine, a safe and easy specimen to test, could offer a cost effective and simple solution to identify patients with tuberculosis. Enzyme linked immunosorbent assays (ELISAs) were performed on concentrated tuberculosis patient urine to detect two M. tuberculosis biomarkers: lipoarabinomannan (LAM) and early secreted antigen-6 kDa (ESAT-6). Concentrating urine improved the detection of LAM in human immunodeficiency virus (HIV) negative patients and patients with a CD4 count > 200 cells/µl. ESAT-6 was not detected by ELISA due to a high background signal caused by the available antibodies cross reacting with a human protein present in urine which was identified by western blot and mass spectrometry. Targeted mass spectrometry did not detect ESAT-6 or its dimer partner, culture filtrate protein-10 kDa (CFP-10) in tuberculosis positive patient urine. Since concentrating urine samples is impractical in a clinical setting a more sensitive diagnostic is needed to detect LAM in urine and ESAT-6 or CFP-10 in other samples. Aptamers can be packed more densely on biosensor surfaces increasing the dynamic range of detection while matching the affinity that an antibody has for a biomarker. Chemically modified DNA aptamers were isolated for LAM and the ESAT-6.CFP-10 dimer. The aptamers were characterised by enzyme linked oligonucleotide assays (ELONAs) and biolayer interferometry. One aptamer bound with high affinity to ESAT-6 while one aptamer bound with low affinity to LAM. The use of aptamers as capture agents for detecting biomarkers in biological specimens thus appears to be a viable option for diagnosing tuberculosis, although availability and concentration of individual biomarkers seems likely to remain key to the choice of specimen in which to make diagnostic measurements.